2017
DOI: 10.3389/fpsyg.2017.01174
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership, Leader-Member Exchange and Feedback Seeking: A Double-Moderated Mediation Model of Emotional Intelligence and Work-Unit Structure

Abstract: This research elucidates the role of ethical leadership in employee feedback seeking by examining how and when ethical leadership may exert a positive influence on feedback seeking. Using matched reports from 64 supervisors and 265 of their immediate employees from a hotel group located in a major city in China, we proposed and tested a moderated mediation model that examines leader-member exchange (LMX) as the mediator and emotional intelligence as well as work-unit structure as double moderators in the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 94 publications
3
34
0
Order By: Relevance
“…In addition, we offer important contributions to the literature on LMX. Most previous research on LMX focuses on how constructive leadership leads to a high-quality leader-member exchange relationship, which then affects employee behaviors and outcomes (Chan and Mak 2012;Lin et al 2018;Qian et al 2017;Wang et al 2005).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we offer important contributions to the literature on LMX. Most previous research on LMX focuses on how constructive leadership leads to a high-quality leader-member exchange relationship, which then affects employee behaviors and outcomes (Chan and Mak 2012;Lin et al 2018;Qian et al 2017;Wang et al 2005).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Second, this study contributes to the LMX literature by exploring the role of LMX in destructive or dark leadership. Indeed, most studies on LMX focus on how constructive leadership leads to a positive and high-quality LMX relationship, which then impacts followers' behavior and outcomes (Chan and Mak 2012;Lin et al 2018;Qian et al 2017;Wang et al 2005). Therefore, exploring and determining how destructive or dark leadership behavior influences the exchange relationship between leaders and followers is imperative (Harvey et al 2007;Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The bootstrapping result for indirect effect between aversive leadership and job performance through work alienation is also significant ( B = −0.07, SE = 0.02, p < 0.05, 95% CI: [−0.06, −0.17]). As far as weak beta coefficient value is concerned, various other studies reported the same in which the beta coefficient for indirect effect was 0.08, 0.03 ( Liu and Li, 2018 ), and 0.08 ( Qian et al, 2017 ) and the results were significant as well. The impact of aversive leadership remained significant on job performance even in the presence of a mediator.…”
Section: Research Design and Methodologymentioning
confidence: 72%
“…The earlier research has also shown that perspective-taking increases the probability of the conversion of creative ideas into more useful products. This conversion occurs because perspectivetaking enables the unbiased selection of good creative ideas and rejection of bad ideas (Dougherty, 1992;Purser et al, 1992). Because perspective taking facilitates better idea selection and idea development, it will lead to a stronger relationship between creative deviance and creative performance.…”
Section: Perspective-takingmentioning
confidence: 99%
“…Since communicative and behavioral norms are parts of the organizational structure, the relationship between LMX and the organizational structure is inherent and intuitive. The mechanistic structure has been established, in the extant literature, as a source of considerable power imbalance between the leader and member, as well as a boundary condition enhancing the negative effects on LMX (see for example, Aryee et al, 2008;Qian et al, 2017). In creative deviance, the employee's neglect of a supervisor's mandate would trigger the supervisor's dissatisfaction; if the supervisor has sufficiently more power in the structure, he/she will express that dissatisfaction in the LMX with impunity.…”
Section: Organizational Structurementioning
confidence: 99%